MANIPULASI LABA SEBELUM DELISTING - Maharani Dhian Kusumawati (Fakultas Bisnis UKDW, 2013)
This study aims to test earnings manipulation by the firm prior delist from the stock exchange in Indonesia, Malaysia, Singapore, and Thailand. Manipulation of earnings used is accrual earnings management and calculate using discretionary accruals. The study found that forced delisted firms and voluntary delisted firms manipulate earnings by income decreasing. Income decreasing in forced delisted firms higher than income decreasing in voluntary delisted firms. Keywords: earnings management¸ delisting, forced delisted, voluntary delisted